End of life care preferences in the Arab population in Israel– bridging the gap between unfounded assumptions and autonomous wishes - Morad Sayid Ahmad; Maya Peled Raz (BMC Medical Ethics)
Abstract Introduction End-of-life (EOL) decision-making involves complex ethical, cultural, and religious considerations, particularly within minority communities. In Israel, the Arab population, comprising approximately 21% of the country’s population, remains underrepresented in EOL research. This study explores the EOL care preferences of elderly Arab individuals and their families, focusing on the interplay between cultural values, religious beliefs, and personal autonomy. Methods A qualitative study was conducted using semi-structured interviews with 24 participants, including elderly individuals (aged 60+) and their family members. Participants were recruited through purposive and snowball sampling in community settings across northern Israel. Data were transcribed, translated, and thematically analyzed to identify key patterns in attitudes toward EOL care. Results Findings reveal a strong preference among elderly Arab participants for a peaceful and dignified death at home rather than in a medicalized setting. Quality of life was prioritized over life-prolonging treatments, with religious beliefs playing a significant role in shaping perspectives. However, cultural taboos and generational differences hindered open communication within families. Many younger family members assumed their elders preferred life extension, while elderly participants often desired comfort-focused care. Additionally, a lack of awareness of advance care planning tools limited the ability of patients to formally express their preferences. Discussion A major challenge identified in this study is the absence of open discussions about EOL preferences, driven by cultural taboos, emotional discomfort, and fear. Many participants avoided such conversations due to beliefs that discussing death invites misfortune or imposes an emotional burden on loved ones. Younger family members, in particular, hesitated to engage in these discussions, leading to decisions based on assumptions rather than explicit patient wishes. Encouraging structured, culturally sensitive conversations and increasing awareness of advance care planning could help ensure that patients’ preferences are recognized and respected. Conclusions Bridging the gap between assumptions and actual preferences requires culturally sensitive communication, increased awareness of advance care planning, and structured family discussions. These measures will ensure that EOL care respects both individual autonomy and cultural values, fostering a more inclusive and patient-centered healthcare approach.